Lower Coverage Rates of Full Rotavirus Vaccine Series in Libyan Children: A Prospective Cross-Sectional Study, 2016 - Salem ALKOSHI; Eyal LESHEM (Tehran University of Medical Sciences, 2020)
Background: There are little data on the current condition of national immunization programme (NIP) in Libya. In 2013, pentavalent rotavirus vaccines were added to the NIP. Incomplete rotavirus vaccine series may result in lower vaccine effectiveness. The study aimed to assess timeliness and coverage rates of routine NIP vaccinations including the newly introduced rotavirus vaccine in Libya. Methods: A prospective cross-sectional study of children aged 0 to 18 months was carried out in vaccination centers of two north-western cities. Data were collected during Nov-Dec 2016 from vaccination cards of children. Child age and doses received in previous visits were documented. Results: Overall, we included 1023 children assessed in 29 visits at six vaccination centers. In children aged 18 months, coverage rates for all doses of BCG, OPV, HepB, pneumococcal, Meningococcal and MMR vaccines exceeded 95%. Coverage rates for second and third doses of rotavirus vaccines were 89% and 68%, respectively. Most (75%) children who missed the third dose of rotavirus vaccine were aged >8 months when at the time of appointment for the third dose. Conclusion: Overall, the coverage rate for routine vaccination in children assessed at immunization centers in northwest Libya was high. Lower coverage of full pentavalent rotavirus vaccine series may have been the result of exceeding the age restriction. Measures to improve timeliness of vaccination appointments should be assessed. Lifting the age restriction on rotavirus vaccines should be considered for at-risk population.